2017
DOI: 10.2147/tcrm.s129910
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for management after thyroidectomy: a retrospective study based on one-center experience

Abstract: Background and aimThe optimal approach to detect and treat symptomatic hypocalcemia (SxH) after thyroidectomy is still uncertain. In our retrospective study, we sought to set a standardized postoperative management protocol on the basis of relative change of parathyroid hormone (PTH) and absolute value of postoperative day 1 (POD1) PTH.MethodsPatients who underwent thyroidectomy were identified retrospectively in our prospective database. Blood was collected 1 day before surgery and on POD1. Extra calcium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…On the other hand, relative parathyroid decline was proved to be a reliable predictor. In our previous preliminary study ( Luo et al, 2017 ), we found that relative 70% decline of PTH was a reasonable indicator of clinical hypocalcemia at 4.67% vs. 27.0% in patients with relative decline of ≤70% and >70%, respectively. Therefore, we hypothesized that PTH relative decline (RDP) may contribute to identifying high-risk patients of hypocalcemia who need calcitriol supplement after thyroidectomy.…”
Section: Introductionmentioning
confidence: 75%
“…On the other hand, relative parathyroid decline was proved to be a reliable predictor. In our previous preliminary study ( Luo et al, 2017 ), we found that relative 70% decline of PTH was a reasonable indicator of clinical hypocalcemia at 4.67% vs. 27.0% in patients with relative decline of ≤70% and >70%, respectively. Therefore, we hypothesized that PTH relative decline (RDP) may contribute to identifying high-risk patients of hypocalcemia who need calcitriol supplement after thyroidectomy.…”
Section: Introductionmentioning
confidence: 75%
“…It can be transient or permanent secondary to hypoparathyroidism [23] . Transient hypocalcemia accounts for 10%-50% of thyroidectomies, and permanent hypocalcemia accounts for up to 2% of cases [24] . The incidence increased after total thyroidectomy, in which transient hypocalcemia occurs in 50%-68% of patients and permanent hypocalcemia occurs in 3% of patients [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding management, all patients with hypocalcemia are treated with calcium supplement orally; for those developing symptoms, an injection of 10% calcium gluconate 10-20 mL is given slowly 2 times a day, with oral administrations of calcium containing vitamin D 3 times a day [30] . If the decrease of postoperative calcium is <70%, the patients could be discharged in the first 24 h following operation, if it is > 70% the patients need longer hospitalization other than calcium supplement [24,31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…Resection of the parathyroid tissue or damage the parathyroid glands during thyroidectomy may result in hypoparathyroidism, resulting in postoperative hypocalcaemia through mechanisms such as inhibition of bone resorption and reduction of 1,25‐dihydroxyvitamin D synthesis by the kidneys 1 . Acute hypocalcaemia impacts up to 50% of thyroidectomy patients and can be permanent in up to 2% of patients 2 . Patients with acute hypocalcaemia may experience symptoms ranging from mild (e.g., paraesthesia of the hands and feet) to severe (e.g., generalized seizures) tetany or they may be asymptomatic, which complicates postoperative management of hypocalcaemia.…”
Section: Introductionmentioning
confidence: 99%
“…1 Acute hypocalcaemia impacts up to 50% of thyroidectomy patients and can be permanent in up to 2% of patients. 2 Patients with acute hypocalcaemia may experience symptoms ranging from mild (e.g., paraesthesia of the hands and feet) to severe (e.g., generalized seizures) tetany or they may be asymptomatic, which complicates postoperative management of hypocalcaemia.…”
Section: Introductionmentioning
confidence: 99%